Efektivitas Program Dana Bantuan Tunai PKH dalam Upaya Pemberdayaan Keluarga Penerima Manfaat di Desa Talaga, Kecamatan Cikupa, Kabupaten Tangerang - Muhammad Rafly Rafsanjani; Syadeli Hanafi; Ahmad Fauzi (MASALIQ, 2025)
This study is motivated by ongoing doubts regarding the effectiveness of the Program Keluarga Harapan (PKH), a conditional cash transfer initiative by the government aimed at alleviating poverty among low-income families. The objective of the research is to assess the effectiveness of PKH cash assistance in empowering Keluarga Penerima Manfaat (KPM) or beneficiary families in Talaga Village, Cikupa Subdistrict, Tangerang Regency. A descriptive qualitative approach was used, with data collected through observation, interviews, and documentation. The findings indicate that the PKH program has been moderately effective in both economic and social empowerment. Its effectiveness is reflected in the accurate targeting of beneficiaries, achievement of program goals, frequency of outreach, and continuity of monitoring efforts. The PKH funds have contributed to meeting the basic needs of KPMs, particularly in education and health sectors. However, challenges remain, including limited community understanding of the program's objectives and instances of misallocation of funds. The study concludes that while PKH has had a positive impact on empowering KPMs, its effectiveness still requires improvement through enhanced outreach, supervision, and the integration of sustainable supporting programs. The implications provide strategic input for local governments and program implementers to improve governance and optimize the benefits of PKH.